PENGARUH BIAYA PRODUKSI DAN BIAYA PEMASARAN TERHADAP PENJUALAN PADA CLASSIE RESTO DI KOTA - Febransyah Febransyah; Anggraini Ewa (Universitas Tridinanti, 2020)
This research basically discusses the effect of production costs and marketing costs on company sales in order to produce reliable information, in this case, the effect of production costs and marketing costs. The place of research in this is Classie Resto Palembang. The purpose of this study was to determine the effect of production and marketing costs on the sales results of Classie Resto in Palembang City.The research sample is the Company's Financial Statements in 2016-2018. Hypothesis testing uses multiple linear regression analysis with the help of the SPSS ver.23 program. Hypothesis testing used includes partial test (t test), simultaneous test (F test), and test the coefficient of determination (R2). The results of hypothesis testing (H1) which states that production costs have a significant effect on sales results received. This can be seen from the results of the SPSS output which shows the t count of the X1 variable is 2.864, which is greater than the t table, which is 2.02809. The results of hypothesis testing (H2) indicate that the marketing costs are significant to the sales results received. This can be seen from the results of the SPSS output which shows the t value of 2.499 is greater than the t table, which is 2.02809 Keywords: Production Costs, Marketing Costs, Sales Results